Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.55705/cmbr.2022.362447.1067
|View full text |Cite
|
Sign up to set email alerts
|

A prospective observational study to assess the cardiac risk factors and treatment patterns in established heart diseases

Abstract: The study aimed to assess established and non-established risk factors and drug therapy problems in the cardiology department and perform a Prospective Observational Study. The study was conducted for a period of 6 months from September 2019 to February 2020 in 200 patients with established heart diseases attending a tertiary care hospital in the cardiology department. A patient interview was conducted using an evaluation form. Among 100 patients with established cardiovascular diseases that were engaged in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
(34 reference statements)
1
0
0
Order By: Relevance
“…It was also uncovered that the protein expressions of p-PI3K and p-AKT were markedly down-regulated in H9c2 cells exposed to nicotine, but they were obviously up-regulated in the cells pre-incubated with Apelin-13 (Figure 5). Related reports have shown that the PI3K/AKT pathway plays a critical role in cellular functions such as cell apoptosis, and it mediates various growth factors to regulate cellular functions by phosphorylating or inhibiting its downstream targets, thereby exerting the regulatory effects of these factors on growth, apoptosis, and survival (20)(21)(22). The above findings are consistent with the results of this study.…”
Section: Discussionsupporting
confidence: 92%
“…It was also uncovered that the protein expressions of p-PI3K and p-AKT were markedly down-regulated in H9c2 cells exposed to nicotine, but they were obviously up-regulated in the cells pre-incubated with Apelin-13 (Figure 5). Related reports have shown that the PI3K/AKT pathway plays a critical role in cellular functions such as cell apoptosis, and it mediates various growth factors to regulate cellular functions by phosphorylating or inhibiting its downstream targets, thereby exerting the regulatory effects of these factors on growth, apoptosis, and survival (20)(21)(22). The above findings are consistent with the results of this study.…”
Section: Discussionsupporting
confidence: 92%
“…The results showed that EMMPRIN expression on the platelet surface and monocyte surface was positively correlated with serum MMPs expression. From the experimental results, we can know that EMMPRIN expression and serum MMPs expression can achieve mutual regulation, which is consistent with previous research results (32)(33). Therefore, in the early diagnosis of ACS, the expression of MMPs in patients can be determined by detecting the expression of EMMPRIN in patients' peripheral blood, and the expression level of EMMPRIN can also be inferred by detecting the expression of MMPs in patients' serum.…”
Section: Discussionsupporting
confidence: 87%
“…Albuquerque et al conducted a study on 111 Brazilian HF patients and concluded the same outcomes (33). Another study was conducted to examine the effect of ACE gene variation on the echocardiographic findings of 103 patients with HF and a lack of association between them was revealed (34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%